Edward Hopper light and dark - Souter, Gerry; ebrary, Inc. (New York : Parkstone International, 2012)
"In his works, Hopper poetically expressed the solitude of man confronted to the American way of life as it developed in the 1920s. Inspired by the movies and particularly by the various camera angles and attitudes of characters, his paintings expose the alienation of mass culture. Done in cold colours and inhabited by anonymous characters, Hopper's paintings also symbolically reflect the Great Depression. Through a series of different reproductions (etchings, watercolours, and oil-on-canvas paintings), as well as thematic and artistic analysis, the author sheds new light on the enigmatic and tortured world of this outstanding figure"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Hopper, Edward, -- 1882-1967 -- Criticism and interpretation; Electronic books